'SUCKING RESULTS OUT OF CHILDREN' REFLECTIVE LIFEWORLD CASE STUDY OF A PRIMARY SCHOOL TEACHER STRIVING FOR AUTHENTICITY. Issue 6 (2nd November 2022) - Plust, Urszula; Joseph, Stephen; Murphy, David
ABSTRACT: This qualitative study presents an analysis of the experiences of a teacher who had recently left working in an England state funded primary school. Using reflective lifeworld methodology, this study explored the teacher's struggle to be authentic in the context of state funded education. Three prominent themes were identified as: 1) enhancement of every learner; 2) systemic oppression; and 3) tensions in being a teacher. The study concludes that being authentic as a teacher was experienced as being incompatible with the current educational system.